Ответ:
г)
Выполним замену:
х²-2 = у
Получим:
у² +3у +2 = 0
По теореме Виета у1= -2; у2 = -1
По обратной подстановке имеем:
х²-2 = -1
х²= 1
х1,2 = +/- 1
или
х²-2 = -2
х² = 0
х = 0
Ответ: -1, 0, 1
1)
![\left \{ {{7x+2y=12} \atop {3x-5y=11}} \right. \\\\\left \{ {{35x+10y=60} \atop {6x-10y=22}} \right. \\\\41x = 82\\x = 2\\\\\\3*2 -10y = 22\\-10 = 10y\\y = -1\\ \left \{ {{7x+2y=12} \atop {3x-5y=11}} \right. \\\\\left \{ {{35x+10y=60} \atop {6x-10y=22}} \right. \\\\41x = 82\\x = 2\\\\\\3*2 -10y = 22\\-10 = 10y\\y = -1\\](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B7x%2B2y%3D12%7D%20%5Catop%20%7B3x-5y%3D11%7D%7D%20%5Cright.%20%5C%5C%5C%5C%5Cleft%20%5C%7B%20%7B%7B35x%2B10y%3D60%7D%20%5Catop%20%7B6x-10y%3D22%7D%7D%20%5Cright.%20%5C%5C%5C%5C41x%20%3D%2082%5C%5Cx%20%3D%202%5C%5C%5C%5C%5C%5C3%2A2%20-10y%20%3D%2022%5C%5C-10%20%3D%2010y%5C%5Cy%20%3D%20-1%5C%5C)
Ответ: (2; -1)
2)
![\left \{ {{x^2+y^2=29} \atop {xy=10}} \right. \left \{ {{x^2+y^2=29} \atop {xy=10}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx%5E2%2By%5E2%3D29%7D%20%5Catop%20%7Bxy%3D10%7D%7D%20%5Cright.)
![\left \{ {{x^2+y^2=29} \atop {2xy=20}} \right. \left \{ {{x^2+y^2=29} \atop {2xy=20}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx%5E2%2By%5E2%3D29%7D%20%5Catop%20%7B2xy%3D20%7D%7D%20%5Cright.)
![\left \{ {{x^2+y^2+2xy=29+20} \atop {xy=10}} \right. \left \{ {{x^2+y^2+2xy=29+20} \atop {xy=10}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx%5E2%2By%5E2%2B2xy%3D29%2B20%7D%20%5Catop%20%7Bxy%3D10%7D%7D%20%5Cright.)
![\left \{ {{(x+y)^2=7^2} \atop {xy=10}} \right. \left \{ {{(x+y)^2=7^2} \atop {xy=10}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B%28x%2By%29%5E2%3D7%5E2%7D%20%5Catop%20%7Bxy%3D10%7D%7D%20%5Cright.)
![\left [ {{\left \{ {{x+y=7} \atop {x=\frac{10}{y}}} \right. } \atop {\left \{ {{x+y=-7} \atop {x=\frac{10}{y} }} \right.}} \right. \left [ {{\left \{ {{x+y=7} \atop {x=\frac{10}{y}}} \right. } \atop {\left \{ {{x+y=-7} \atop {x=\frac{10}{y} }} \right.}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5B%20%7B%7B%5Cleft%20%5C%7B%20%7B%7Bx%2By%3D7%7D%20%5Catop%20%7Bx%3D%5Cfrac%7B10%7D%7By%7D%7D%7D%20%5Cright.%20%7D%20%5Catop%20%7B%5Cleft%20%5C%7B%20%7B%7Bx%2By%3D-7%7D%20%5Catop%20%7Bx%3D%5Cfrac%7B10%7D%7By%7D%20%7D%7D%20%5Cright.%7D%7D%20%5Cright.)
![\left [ {{\left \{ {{10+y^2=7y} \atop {x=\frac{10}{y}}} \right. } \atop {\left \{ {{10+y^2=-7y} \atop {x=\frac{10}{y} }} \right.}} \right. \left [ {{\left \{ {{10+y^2=7y} \atop {x=\frac{10}{y}}} \right. } \atop {\left \{ {{10+y^2=-7y} \atop {x=\frac{10}{y} }} \right.}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5B%20%7B%7B%5Cleft%20%5C%7B%20%7B%7B10%2By%5E2%3D7y%7D%20%5Catop%20%7Bx%3D%5Cfrac%7B10%7D%7By%7D%7D%7D%20%5Cright.%20%7D%20%5Catop%20%7B%5Cleft%20%5C%7B%20%7B%7B10%2By%5E2%3D-7y%7D%20%5Catop%20%7Bx%3D%5Cfrac%7B10%7D%7By%7D%20%7D%7D%20%5Cright.%7D%7D%20%5Cright.)
![10+y^2-7y = 0 10+y^2-7y = 0](https://tex.z-dn.net/?f=10%2By%5E2-7y%20%3D%200)
y1 = 2; y2=5 => x1 = 5; x2 = 2
![10+y^2+7y = 0 10+y^2+7y = 0](https://tex.z-dn.net/?f=10%2By%5E2%2B7y%20%3D%200)
y1 = -2; y2 = -5 => x1 = -5; x2 = -2
Ответ: (-5: -2), (-2: -5), (2: 5), (5: 2).
Объяснение:
както так